2022
DOI: 10.1017/s0142716422000200
|View full text |Cite
|
Sign up to set email alerts
|

The offline and online effects of processing instruction

Abstract: The present study investigated the effects of processing instruction (PI) on the acquisition of accusative case markers in German, focusing on whether PI influences learners’ online processing behaviors. Third and fourth semester L1 English-L2 German learners were divided into two groups: a traditional instruction (TI) group and a PI group. Participants completed offline sentence interpretation and production tasks, as well as a self-paced reading (SPR) task, which provides a detailed investigation of how PI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…A two-way ANOVA was performed to find the efficacy of PI and output-oriented activities in learning the future tense of English. The obtained statistics indicated that both PI and output groups outperformed research reported earlier (e.g., [13,58,59,62,65,67]). However, Birjandi and Rahemi [62] reported that on tasks requiring interpretation, both PI and output group outperformed the explicit group, however on tasks requiring production, the output group beat both PI and explicit groups.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…A two-way ANOVA was performed to find the efficacy of PI and output-oriented activities in learning the future tense of English. The obtained statistics indicated that both PI and output groups outperformed research reported earlier (e.g., [13,58,59,62,65,67]). However, Birjandi and Rahemi [62] reported that on tasks requiring interpretation, both PI and output group outperformed the explicit group, however on tasks requiring production, the output group beat both PI and explicit groups.…”
Section: Discussionsupporting
confidence: 62%
“…According to VanPatten [9], PI is a psycholinguistically inspired strategy to FonF whose primary goal is to teach grammar without abandoning either communication or learningcentered activities and finally leads students to practice grammar. All in all, PI has been proved to be a fruitful teaching strategy [13,44,45].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few studies have used cognitive behavioral measures such as self-paced reading (SPR) or eye-tracking to investigate how PI and related instructional interventions change learners' processing strategies, though these methodologies are becoming more common in PI research. As Lee et al (2020) and Henry (2022) discuss, these studies address an increasingly large number of research questions, but many have centered on the effects of PI compared to other instructional trainings (Benati, 2020a(Benati, , 2020bChiuchiù & Benati, 2020;Henry, 2022;Issa & Morgan-Short, 2019;McManus & Marsden, 2017Wong & Ito, 2018) and on aspects of a PI training, such as the delivery of explicit information (EI) or feedback (Dracos & Henry, 2018;Indrarathne & Kormos, 2017;Issa, 2019;Wong & Ito, 2018). While these studies have utilized a variety of methodological approaches, the research has broadly found that PI increases attention and sensitivity to the target forms (Henry, 2022;Issa & Morgan-Short, 2019), reduces the use of nontarget processing strategies (Dracos & Henry, 2018;Wong & Ito, 2018), and/or increases depth or ease of processing (Chiuchiù & Benati, 2020;Lee et al, 2020).…”
Section: The Effects Of Training On Processingmentioning
confidence: 99%
“…One recent study by Henry (2022) investigated whether PI pushes learners to process nominative and accusative case markers in German online. Two groups were instructed on German case markers using either PI or a traditional output-focused instruction (TI) and completed an online SPR task.…”
Section: The Effects Of Training On Processingmentioning
confidence: 99%